Another look at the foramen magnum in bipedal mammals. Issue 105 (April 2017) - Russo, Gabrielle A.; Kirk, E. Christopher
Abstract: A more anteriorly positioned foramen magnum evolved in concert with bipedalism at least four times within Mammalia: once in macropodid marsupials, once in heteromyid rodents, once in dipodid rodents, and once in hominoid primates. Here, we expand upon previous research on the factors influencing mammalian foramen magnum position (FMP) and angle with four new analyses. First, we quantify FMP using a metric (basioccipital ratio) not previously examined in a broad comparative sample of mammals. Second, we evaluate the potential influence of relative brain size on both FMP and foramen magnum angle (FMA). Third, we assess FMP in an additional rodent clade (Anomaluroidea) containing bipedal springhares ( Pedetes spp.) and gliding/quadrupedal anomalures ( Anomalurus spp.). Fourth, we determine the relationship between measures of FMP and FMA in extant hominoids and an expanded mammalian sample. Our results indicate that bipedal/orthograde mammals have shorter basioccipitals than their quadrupedal/non-orthograde relatives. Brain size alone has no discernible effect on FMP or FMA. Brain size relative to palate size has a weak influence on FMP in some clades, but effects are not evident in all metrics of FMP and are inconsistent among clades. Among anomaluroids, bipedal Pedetes exhibits a more anterior FMP than gliding/quadrupedal Anomalurus . The relationship between FMA and FMP in hominoids depends on the metric chosen for quantifying FMP, and if modern humans are included in the sample. However, the relationship between FMA and FMP is nonexistent or weak across rodents, marsupials, and, to a lesser extent, strepsirrhine primates. These results provide further evidence that bipedal mammals tend to have more anteriorly positioned foramina magna than their quadrupedal close relatives. Our findings also suggest that the evolution of FMP and FMA in hominins may not be closely coupled.